ANALISIS KONEKSI MATEMATIS DAN BERPIKIR KRITIS SISWA KOGNITIF TINGGI PADA MASALAH MATEMATIKA HOTS - Rismawati, Melinda; Andri, Andri; B Rindiani, Anita; Wahyudi (Department of Mathematics Education , University of Jember, 2025)
This study aims to describe students' mathematical connections and critical thinking in solving math problems based on HOTS questions in class X SMA Negeri 4 Sintang. The method used in this research is a descriptive qualitative approach. Data collection techniques used observation, interviews, and documentation techniques. The data analysis techniques used in this study are data collection, data reduction, data presentation, and conclusion drawing. Based on the results of data analysis, the structure of mathematical connections and critical thinking of students in solving HOTS problems in the low category, the most mistakes made by students in the indicators of mathematical connections, namely using the connection between mathematical ideas and understanding how mathematical ideas are connected to solve problems. In critical thinking, namely forming basic skills, providing further explanation, drawing conclusions on HOTS questions, only some students can work at this stage. The conclusions of this study are: (1) in question 1 the subject fulfills the indicators of mathematical connection and critical thinking to solve the problem, (2) in question 2 the subject SAL can determine the solution correctly (3) in question 3 the subject SAL answers less precisely.